2018
DOI: 10.5751/es-10280-230323
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers in socio-environmental research: components, connections, scale, and context

Abstract: ABSTRACT. The complex and interdisciplinary nature of socio-environmental (SE) problems has led to numerous efforts to develop organizing frameworks to capture the structural and functional elements of SE systems. We evaluate six leading SE frameworks, i.e., human ecosystem framework, resilience, integrated assessment of ecosystem services, vulnerability framework, coupled human-natural systems, and social-ecological systems framework, with the dual goals of (1) investigating the theoretical core of SE systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 60 publications
(112 reference statements)
0
31
0
3
Order By: Relevance
“…widely used among CPR scholars and found no single framework sufficient to address all CPR-related research questions. Pulver et al (2018) in a follow up study of 6 other frameworks 4 confirmed this result and highlighted a trade-off between generality in theory and context specificity in application. Existing frameworks in the study of CPR governance differ in their conceptualization, goal and applicability, and temporal, social, and spatial scale addressed (Binder et al 2013;Pulver et al 2018).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…widely used among CPR scholars and found no single framework sufficient to address all CPR-related research questions. Pulver et al (2018) in a follow up study of 6 other frameworks 4 confirmed this result and highlighted a trade-off between generality in theory and context specificity in application. Existing frameworks in the study of CPR governance differ in their conceptualization, goal and applicability, and temporal, social, and spatial scale addressed (Binder et al 2013;Pulver et al 2018).…”
Section: Introductionmentioning
confidence: 71%
“…Pulver et al (2018) in a follow up study of 6 other frameworks 4 confirmed this result and highlighted a trade-off between generality in theory and context specificity in application. Existing frameworks in the study of CPR governance differ in their conceptualization, goal and applicability, and temporal, social, and spatial scale addressed (Binder et al 2013;Pulver et al 2018). Such differences may result, as McGinnis and Ostrom (2014) noted, from "investment in updating and improving" a framework.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The authors argued that traditional location-specific studies were unable to pick out the complex cross-system configurations that may underlie human-environment interactions over distances. Further highlighting this tendency to focus on a single location, analytical tools available to social science researchers typically overlook the influences from external systems [40]. For smallholder studies, the integration in the globalized world is often overlooked, and most smallholder perspectives focus on their local context/conditions (place-based) without considering how flows/interactions with external systems affect these location-specific outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…L. Turner et al, 2003;Billie Lee Turner et al, 2003) may provide the most fruitful analytical approach to understanding such interactions, especially in the Anthropocene during which we may face surprises founded on and amplified by the increasingly tight coupling of earth and social systems, more likely to cross thresholds into novel states (Steffen et al, 2015) . However, socio-environmental thinking and theory (Pulver et al, 2018) have yet to be fully applied to understanding extreme events. Further, natural science exploration tends to constrain analysis to the interacting elements on the biophysical side (Gill & Malamud, 2014) , and study of social impacts tend to focus on individual events or hazards (Colten, 2009;Klinenberg, 2003;Kreibich et al, 2014;Meyer et al, 2013) , neglecting the interacting factors that lead to extreme outcomes.…”
Section: Introduction: Going To Extremesmentioning
confidence: 99%